2015
DOI: 10.14241/asgp.2015.016
|View full text |Cite
|
Sign up to set email alerts
|

Stability of monazite and disturbance of the Th-U-Pb system under experimental conditions of 250–350 °C and 200–400 MPa

Abstract: Ab stract: This ex per i men tal study pro vides im por tant data fill ing the gap in our knowl edge on monazite sta bil ity un der con di tions of fluid-me di ated low-tem per a ture meta mor phic al ter ation and post-mag matic hy dro ther mal al ter ations. The sta bil ity of monazite and main te nance of orig i nal Th-U-to tal Pb ages were tested ex per i men tally un der P-T con di tions of 250-350 °C and 200-400 MPa over 20-40 days. The start ing ma te ri als in cluded the Bur net monazite + K-feld spar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…This compositional de pend ence was later con firmed ex per i men tally across a wider P-T range of 200-1000 MPa and 450-750°C by the al ter ation of monazite to al la nite and ap a tite or britholite . Re cent ex per i ments con ducted at 250-350°C and 200-400 MPa did not re sult in al ter ation of monazite, which sug gests that monazite re mains sta ble in high-Ca bulk com po si tion un der low-tem per a ture con di tions (Budzyñ et al, 2015b).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…This compositional de pend ence was later con firmed ex per i men tally across a wider P-T range of 200-1000 MPa and 450-750°C by the al ter ation of monazite to al la nite and ap a tite or britholite . Re cent ex per i ments con ducted at 250-350°C and 200-400 MPa did not re sult in al ter ation of monazite, which sug gests that monazite re mains sta ble in high-Ca bulk com po si tion un der low-tem per a ture con di tions (Budzyñ et al, 2015b).…”
Section: Introductionmentioning
confidence: 85%
“…The fluid-me di ated com plete re moval of Pb in al tered monazite do mains pro vides a pow er ful tool for dat ing metasomatic and hy dro ther mal processes, as was ex per i men tally dem on strated at 450°C and 450 MPa . Re cent ex per i ments at 250-350°C and 200-400 MPa showed that the al kali-bear ing en vi ron ment pro motes dis so lu tion-reprecipitation al ter ation of monazite with only par tial Pb re moval (Budzyñ et al, 2015b). The lat ter case has far im pli ca tions to geo chron ol ogy re gard ing post-mag matic pro cesses that may af fect monazite and re sult in geo log i cally mean ing less, dis turbed Th-U-Pb dates.…”
Section: Monazite In Metamorphic Rocksmentioning
confidence: 97%
See 2 more Smart Citations
“…Four gently flat tened cap sules, two for xeno time ex per i ments with 2M Ca(OH) 2 and Na 2 Si 2 O 5 + H 2 O flu ids, and two for "twin" ex per i ments on monazite (Budzyñ et al, 2013(Budzyñ et al, , 2015, were placed in each au to clave. Three sets of ex per i ments were run un der P-T con di tions and with a du ra tion of: (1) Du ra tions of the ex per i ments were cho sen based on pre vi ous ex per i ments on the sta bil i ties of monazite and xeno time (Hether ing ton et al, 2010;Harlov et al, 2011).…”
Section: Experimental and Analytical Methods Experimental Methodsmentioning
confidence: 99%